Characterization of Humic Acids and Fulvic Acids Derived from Sewage Sludge - Li*, H.; Li, Y.; Li, C. (Asian Journal of Chemistry, 2013)
A comparative study of sludge humic acids and fulvic acids was carried out by means of elemental analysis, functional analysis, infrared spectroscopy and ultrafiltration fractionation. The result showed that humic acid was the main composition of sludge humic substances and fulvic acid was only one eighth of humic acid. 49.3 % of sludge humic acid and 88.9 % of sludge fulvic acid were extracellular substances. Sludge fulvic acid has more oxygen functional groups, fewer hydrocarbons, less aliphatic and aromatic structure and smaller molecular size than sludge humic acid. 37.7 % of fulvic acid had molecular weight of 30-50 kDa and 87.8 % of humic acid had molecular weight higher than 100 kDa. The fraction with small molecular sizes contained less condensed aromatic rings than aliphatic structures.